Exploring the seasonal relationship between spatial and temporal features of land surface temperature and its potential drivers: the case of Chengdu metropolitan area, China - Hu, Chunguang; Huang, Gaoliu; Wang, Zhiyong (Frontiers in Earth Science, 2023)
Global climate change and the process of urbanization have had a significant impact on land surface temperature (LST). This study selects the Chengdu metropolitan area in China as a typical research subject. Based on the seasonal heterogeneity and spatial distribution characteristics of LST, different types of potential influencing factors are selected for Principal Component Analysis (PCA) to determine the categories of these factors. Subsequently, a multiple linear regression analysis is conducted to explore the relationship between LST and the identified potential influencing factors during different seasons. The findings of this study suggest that the regions with high temperatures and secondary high temperatures in the Chengdu metropolitan area are primarily concentrated in Chengdu and its adjacent localities, exhibiting noticeable seasonal variations. In the summer, high-temperature zone and second high-temperature zone of the LST show a central aggregation pattern. In the transition season, the high-temperature zone of the LST presents a “large dispersion, small aggregation” pattern. In the winter, it presents a dispersed pattern. In terms of influencing factors, elevation, slope, wind speed, humidity, and surface vegetation cover related to natural geographical conditions have a significant impact on LST, reaching a peak during the transition season. Factors associated with social and economic conditions, such as population size, nighttime light index, and road density, have a pronounced effect on LST during the summer season. During winter, LST is mainly influenced by landscape pattern-related factors such as Shannon Diversity Index, Edge Density, Largest Patch Index, and Patch Density. This study not only assesses the seasonal and spatial characteristics of LST in the Chengdu metropolitan area but also provides valuable insights for formulating phased measures to mitigate the Urban Heat Island (UHI) in other regions.